Healthcare Value Proposition : Creating a Culture of Excellence in Patient Experience. - Omachonu, Vincent K. (Milton : Productivity Press, 2018)
Never before in the healthcare industry has there been such intense emphasis and open debate on the issue of quality. The steady rise in the cost of healthcare coupled with the need for quality have combined to put the healthcare industry at the top of the national agenda. Quality, costs, and service are not just socially provocative ideas. They are critical criteria for decision-making by patients, physicians, and many key constituents of healthcare organizations. The pursuit of improved performance has driven a host of executives and managers in search of techniques for structuring, rehabilitating, redesigning, and reengineering the organizations they serve. Unfortunately, the narrow-mindedness with which programs are implemented and the discontinuity in their application weaken the promise of success. The process of quality improvement can become an undisciplined search for illusions rather than reality. For many years, healthcare managers have embraced the narrow definition of performance solely in the context of financial success. Forward-thinking executives now realize that the road to financial success begins with success in quality and service. Quality and service are no longer separate issues - they are the same. Neither one by itself will bring about lasting success. The ultimate measure of performance is in an organization's ability to create value for its customers, and true performance must be measured in the context of the customers' total experience. This book is about how to manage performance in the context of value to the customer or patient. It brings together the many pieces of the performance improvement puzzle - quality, technology, costs, productivity, and customer service. The author also covers process improvement tools including Lean and Six Sigma, and how to create a culture of continuous improvement as well as how to improve the patient experience and productivity improvement strategies. The book is filled with examples, illustrations, and tools for improving key aspects of a healthcare organization's performance.
Plan Its ImplementationDay 4-Implement the Future State; Day 5-Operationalize the Future State and Debrief; The Five S Method; Planning for 5S; The Steps for Implementing 5S Methodology; Benefits of 5S; SMED; Examples of SMED Healthcare Applications; Five Whys; Kanban; Steps for the Implementation of a Two-Bin Kanban System; Benefits of Kanban in Hospitals and Clinics; Standardized and Standard Work; The Process; Benefits of Standardized Work; Questions for Discussion; References; Additional Readings; 7: Six Sigma; Key Concepts of Six Sigma; Examples of Defects; Control Charts; Control Charts for Attribute Data.
OCLC-licensed vendor bibliographic record.
Keywords: Medical care -- Quality control; MEDICAL -- Administration; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Industries -- Service Industries